Erbium-doped nanocrystalline silicon thin films produced by RF sputtering - Annealing effect on the Er emission - Cerqueira, M.F.
In the present work, erbium doped nanocrystalline silicon thin films were produced by reactive magnetron sputtering on glass substrates under different conditions (substrate temperature and Er content). The film structure was studied using Raman spectroscopy. The chemical composition was determined using the RBS technique. All the samples show sharp 4I13/2 → 4I15/2 intra-4f11 emission of Er 3+ related centres with its maximum positioned at the1.54 μm. However, the intensity of this transition (strongly dependent on the chemical composition of the matrix where the nanocrystals are embedded in and also on the structure of the matrix) changes after thermal annealing treatment. For the less crystalline samples our results show an increase of the Er3+ PL intensity and for the highly crystalline ones the Er emission vanishes even at low temperature. This behaviour was studied and explained in this work, on the basis of energy transfer between Si and Er ions.